Caracterização ambiental da reserva extrativista Chico Mendes (Acre-Brasil): subsídios ao plano de manejo - Costa, Suely de Souza Melo da (Universidade Federal de São Carlos, 2000)
The main objective of this work was the environmental characterization of 'Reserva Extrativista Chico Mendes , a Protected Area located in the state of Acre, Brazil. This analysis had a view to achieving a general diagnosis of the reserve environmental situation in the face of patterns of land and resource utilization and to providing an ecological basis for the planning of the sustainable exploitation of its natural resources. The methodology employed in this work involved the elaboration of a georeferenced digital data bank with thematic maps and morphometric information on hydrography, elevation, slope, soils, roads and human activities within the reserve area and in its surroundings (10 km buffer zone). Landscape structural elements were analyzed in 3 hydrographic basins identified in the hydrography map. These basins were further divided into 4 management units on which our study was focused. Our results show that RECM presents only 1% of its area modified by anthropic activities, heterogeneously distributed throughout the reserve and mainly associated to the location of colocações. The reserve surroundings have 16, 73% of its area modified by anthropic activities mainly located south and southeastern to the reserve. Predominant land uses in these areas constitute extensive cattle-raising and agriculture. We conclude from this analysis that the RECM has been playing its role as a Protected Area of sustainable use, particularly due to its great extension and low human demographic density. However its surroundings are fairly overtaken by various anthropic activities what suggests an urgent need for observing legal aspects of land utilization in the 10 km buffer zone around the reserve as well as constantly monitoring human activities within this zone and in its surroundings.
Keywords: Ecologia; Política ambiental; Diagnóstico ambiental; Unidades de Gerenciamento; Sistema de informação geográfica; Ação antrópica; Gestão ambiental; CIENCIAS BIOLOGICAS::ECOLOGIA